Physical, chemical, and biological control of black rot of brassicaceae vegetables: A review - Liu, Zeci; Wang, Huiping; Wang, Jie; Lv, Jian; Xie, Bojie; Luo, Shilei; Wang, Shuya; Zhang, Bo; Li, Zhaozhuang; Yue, Zhibin; Yu, Jihua (Frontiers in Microbiology, 2022)
As one of the important sources of human nutrition, Brassicaceae vegetables are widely grown worldwide. Black rot caused by Xanthomonas campestris pv. campestris (Xcc) seriously affects the quality and yield of Brassicaceae vegetables. Therefore, it is important to study control methods of Xcc for Brassicaceae vegetable production. This paper reviews the physical, chemical, and biological control methods of Xcc in Brassicaceae vegetables developed in recent years, and the underlying mechanisms of some control methods are also discussed. Based on our current knowledge, future research directions for Xcc control are also proposed. This review also provides a reference basis for the control of Xcc in the subsequent field cultivation of Brassicaceae vegetables.